Who benefits from regular class participation?. Issue 3 (13th August 2020) - Tang, Lei; Li, Shanshan; Auden, Emma; Dhuey, Elizabeth
Abstract: In this study, the authors investigated three questions: whether students' outcomes were improved by grading participation more intensely; who benefits most from increased participation; and, whether students who would benefit from more intensive grading choose it when they are given the choice. An eight-month field experiment was used to elicit students' preferences for and randomly assign them to different grading intensities. The authors found that grading students on weekly participation is more effective than biweekly and that students who prefer not to be graded weekly, with lower GPAs and lower self-control scores, benefit most from the weekly participation grading intervention. When students were given a choice, however, those who would benefit the most were no more likely to choose weekly grading than were others.